294-OR: Tirzepatide Prevents Palmitate-Induced Apoptosis, Autophagy, and Senescence in Human Cardiac Progenitor Cells - COLABUFO, CARMELA; CALDERONI, ISABELLA; DORIA, ROSSELLA; CACCIOPPOLI, CRISTINA; PALMA, GIUSEPPE; SANTARPINO, GIUSEPPE; BOTTIO, TOMASO; MILANO, ALDO D.; LEONARDINI, ANNA; NATALICCHIO, ANNALISA; PERRINI, SEBASTIO; CIGNARELLI, ANGELO; et al. (Diabetes (New York, N.Y.), 2025)
Introduction and Objective: Tissue turnover in the human heart requires the recruitment of multipotent cardiac progenitor cells (hCPC). Defective hCPC number and pro-angiogenic capacity contribute to diabetes- and obesity-related heart failure in humans. Evidence supports potential cardiovascular benefits of dual GIP/GLP-1 receptor agonists. The aim of this study was to evaluate whether hCPC express functional GLP-1R and GIPR, and to investigate the ability of the GIP/GLP-1 receptor agonist tirzepatide to prevent palmitate-induces apoptosis, autophagy, and senescence in hCPC. Methods: hCPC were obtained from right auricle biopsies of non-obese, non-diabetic subjects undergoing elective cardiac surgery. GLP-1R and GIPR mRNA and protein expression were demonstrated by quantitative real-time PCR and immunoblotting, respectively. hCPC, pretreated or not with 100 nM tirzepatide for 1 h, were exposed to 0.25 mM palmitate for 16 h. CREB phosphorylation was evaluated by immunoblotting. Apoptosis, autophagy and senescence, were evaluated by cleaved caspase-3, LC3-II and p21Cip1/WAF1 immunoblotting, respectively. Results: hCPC express both functional GLP-1R and GIPR. Exposure of hCPC to tirzepatide for 5 min activated CREB (p<0.05). Treatment of hCPC with palmitate induced apoptosis, autophagy and senescence (p<0.05). Pretreatment of hCPC with tirzepatide prevented palmitate-induced apoptosis, autophagy, and senescence (p<0.05). Conversely, the GLP-1R agonist exendin-4 prevented palmitate-induced apoptosis and autophagy, whereas GIP prevented apoptosis, but not autophagy. Conclusion: hCPC express functional GLP-1R and GIPR that mediate partially overlapping bioeffects. Tirzepatide prevents palmitate-induced apoptosis, autophagy, and senescence of hCPC, showing that dual pharmacological targeting through both GLP-1R and GIPR might be required to exert full beneficial effects on hCPC survival and function.